Functional Analysis of the Differences in the Dimensions of Two Types of Boiled and Steamed Rice Grains - Mirosław Krzyśko; Waldemar Wołyński; Marek Domin; Zofia Hanusz; Leszek Rydzak; Łukasz Smaga; Andrzej Wojtyła (International Journal of Food Science)
The study tested how the cooking process can change the dimensions of rice grains. The impact of set times of cooking or steaming process on the characteristics such as length, width, and height of two varieties of rice, namely, long-grain white and parboiled, was investigated. The measurements of the dimension characteristics obtained at different times of the cooking process were converted to functional data. Different methods of multivariate functional data analysis, namely, functional multivariate analysis of variance, functional discriminant coordinates, and cluster analysis, were applied to discover the differences between the two varieties and the two heat treatment methods.